2021
DOI: 10.1155/2021/6654718
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Logistics for Solid Waste from the Construction Industry

Abstract: This article reviews studies on the application of reverse logistics in solid waste from the construction industry. The main objective is to provide a summary of current knowledge and specific areas for future research. In addition, construction, as an economic sector, is in a continuous search for new tools to improve its processes, so this research provides the current situation of the relationship between reverse logistics and solid waste in the industry. The review methodology was content analysis of scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…According to this survey, the legislative drive aids in the improvement of waste management to boost company performance. This study's findings are consistent with [58,60,61], which suggested that businesses are affected by regulatory and environmental legislation. The chi-square statistic would seem in the value column right portion of "Pearson chisquare" in the result shown in Table 14.…”
supporting
confidence: 86%
“…According to this survey, the legislative drive aids in the improvement of waste management to boost company performance. This study's findings are consistent with [58,60,61], which suggested that businesses are affected by regulatory and environmental legislation. The chi-square statistic would seem in the value column right portion of "Pearson chisquare" in the result shown in Table 14.…”
supporting
confidence: 86%
“…trust and awareness of collaboration benefits ) were not observed as determinants of external stakeholders' influence strategies in RLSC in CI. This observation is permissible as it has already been found that the entire construction supply chain has a reputation for low trust and adverse relationships between different stakeholders (van den Berg et al , 2020; Vargas et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used for analyzing the studies is the systematic literature review (SLR) used by [5,[75][76][77][78][79][80][81]. This document integrates and relates 14 technological trends linked to I4.0 with three thematic areas: financial (FI), operational (OP), and sustainable (SU).…”
Section: Methodsmentioning
confidence: 99%